Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Prajurit Satuan Kapal Eskorta Koarmada II - Suyadi; Yanu Madawanto; Salim (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Escort ship is a warship designed for the duties of guarding and protecting a main body or not of high value when a formation is carrying out sea crossing tasks. The Escort ship is also the main element of the convoy's protection. The crew member factor is a determinant of the ability level of the Escort Ship Unit and the readiness of other equipment. As the main factor, human resource must have high quality, readiness and discipline. Each individual and group must be skilled and work, and have good discipline. The existence of discipline and individual performance of the Escort Ship Unit and related to the terrain in the ship's environment and at sea, with the terrain situation being subject to change at any time, the Indonesian Navy carries out various organizational restructuring efforts which are expected to also contribute to the quality of its personnel. One of them is through training for mature provisions in the given field. The purpose of this study was to test and analyze the effect of training and discipline simultaneously on the performance of the 2nd Fleet Command Escort Ship Unit soldiers, to test and analyze the effect of training partially on the performance of the 2nd Fleet Command Escort Ship Unit soldiers, to test and analyze the effect of discipline partially on the performance of the Satkor Koarmada II soldiers. This research approach uses quantitative methods, namely methods that use the number of samples and numerical data. The results showed that the Training and discipline simultaneously and partial have a significant effect on the performance of the 2nd Fleet Command Escort Ship Unit Soldiers. From the results of this study, it can be said that training and discipline can improve the performance of the 2nd Fleet Command Escort Ship Unit in carrying out training.